Regulatory B Cells and Tolerance in Transplantation: From Animal Models to Human - Chesneau, Melanie; Michel, Laure; Degauque, Nicolas; Brouard, Sophie (Frontiers in Immunology, 2013)
Until recently, the role of B cells in transplantation was thought to be restricted to producing antibodies that have been clearly shown to be deleterious in the long term, but, in fact, B cells are also able to produce cytokine and to present antigen. Their role as regulatory cells in various pathological situations has also been highlighted, and their role in transplantation is beginning to emerge in animal, and also in human, models. This review summarizes the different studies in animals and humans that suggest a B-cell regulatory role in the transplant tolerance mechanisms.